KONSTRUKSI MODERASI BERAGAMA MASYARAKAT SALATIGA SEBAGAI KOTA TOLERAN - Fibry Jati Nugroho; Dwi Novita Sari; Agustinus Tunda (Manna Rafflesia, 2025)
This article presents the construction of society in Salatiga in realizing tolerance and moderate religious life. Salatiga, which has received the title of being a tolerant city in Indonesia, is important to study regarding the existing social construction, so that for several years in a row it has been ranked in the top three. Using a qualitative approach, qualitative descriptive methods and data collection through observation, interviews accompanied by Focus Group Discussions, then analyzed using the Miles and Huberman model. The findings of this research show that basic construction in society is formed from local history, education, community meeting spaces and economic activities to become social capital that continues to maintain and develop tolerance in Salatiga. Religious moderation introduced by the government has been implemented in Salatiga City.